2010
DOI: 10.1111/j.1471-4159.2010.06726.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurites regrowth of cortical neurons by GSK3β inhibition independently of Nogo receptor 1

Abstract: J. Neurochem. (2010) 113, 1644–1658. Abstract Lesioned axons do not regenerate in the adult mammalian CNS, owing to the over‐expression of inhibitory molecules such as myelin‐derived proteins or chondroitin sulphate proteoglycans. In order to overcome axon inhibition, strategies based on extrinsic and intrinsic treatments have been developed. For myelin‐associated inhibition, blockage with NEP1–40, receptor bodies or IN‐1 antibodies has been used. In addition, endogenous blockage of cell signalling mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 88 publications
(190 reference statements)
1
13
0
Order By: Relevance
“…6), and was significantly worse than that induced by p25 plus CDK5. Consistent with previous findings (22,50), our data therefore suggests aberrant activity of GSK3β can also lead to loss of neurite arborization.…”
Section: Gsk3β Specifically Interacts With P25 But No Other Cyclins Isupporting
confidence: 93%
“…6), and was significantly worse than that induced by p25 plus CDK5. Consistent with previous findings (22,50), our data therefore suggests aberrant activity of GSK3β can also lead to loss of neurite arborization.…”
Section: Gsk3β Specifically Interacts With P25 But No Other Cyclins Isupporting
confidence: 93%
“…In addition, SB-216763 was shown to inhibit axon growth in postnatal and embryonic DRG neurons (Owens et al, 2003; Alabed et al, 2011). On the other hand, different studies reported that SB-216763 induced the formation of multiple long axons in hippocampal, cerebellar granular (CG), and DRG neurons (Padilla et al, 1997; Jiang et al, 2005; Yoshimura et al, 2005; Seira et al, 2011). Furthermore, it improved axon regeneration in lesioned neurons (Seira et al, 2011).…”
Section: Organic Molecules As Gsk-3 Inhibitorsmentioning
confidence: 99%
“…CSPG and OMgp proteins were purchased from R&D Systems (Minneapolis, MN, USA). Myelin extract was obtained as [40] and NogoA-containing membranes as [41].…”
Section: Antibodies and Biochemical Reagentsmentioning
confidence: 99%
“…Cells were placed in 24-well tissue culture dishes (Nunc, Roskilde, Denmark) on coated coverslips (see below) and grown for 24-48 h in DMEM medium supplemented with N2 and B27 (Invitrogen). The procedures were used to treat cells with MAIs or myelin; the cell surface was coated with purified myelin essentially as described [40]. In vitro experiment on microfluidic devices Embryonic cortical neurons were cultured in compartmented microchips (Cat.…”
Section: Nogo66-ap Binding Assaysmentioning
confidence: 99%